2016
DOI: 10.1186/s12913-016-1694-x
|View full text |Cite
|
Sign up to set email alerts
|

Working relationships between obstetric care staff and their managers: a critical incident analysis

Abstract: BackgroundMalawi continues to experience critical shortages of key health technical cadres that can adequately respond to Malawi’s disease burden. Difficult working conditions contribute to low morale and frustration among health care workers. We aimed to understand how obstetric care staff perceive their working relationships with managers.MethodsA qualitative exploratory study was conducted in health facilities in Malawi between October and December 2008. Critical Incident Analysis interviews were done in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 50 publications
2
29
0
3
Order By: Relevance
“…Notwithstanding its high perception, interactional justice was limited by reduced information sharing with, and lack of respect for subordinates, by supervisors among all professional sub-groups. Our findings support the evidence that health managers tend to be unsupportive, lack respect for junior staff and provide negative feedbacks during supervision [2,4,[18][19][20][21][23][24][25][26][27]. The study further revealed that nurses and AHPs had significantly lower perception of interactional justice than doctors, which contrasts insignificant differences in interactional justice between doctors and non-doctors found in a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Notwithstanding its high perception, interactional justice was limited by reduced information sharing with, and lack of respect for subordinates, by supervisors among all professional sub-groups. Our findings support the evidence that health managers tend to be unsupportive, lack respect for junior staff and provide negative feedbacks during supervision [2,4,[18][19][20][21][23][24][25][26][27]. The study further revealed that nurses and AHPs had significantly lower perception of interactional justice than doctors, which contrasts insignificant differences in interactional justice between doctors and non-doctors found in a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 87%
“…Perception of unfairness in salaries decreased perception of distributive justice among healthcare professionals [3,11,[13][14][15][16][17][18][19][20]. In Tanzania, the experience of being by-passed by colleagues with shorter working experience and longer formal training was most dissatisfying for health workers with longer working experience [14].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars of social support agreed that the concept is a positive tool to enhance interpersonal relationships among cadres of employees (Chipeta, Bradley, Chimwaza-Manda & McAuliffe, 2016). The general concern is whether all employees have uniform perception towards helpful assistance available from the organisation through supervisors and colleagues, or not (Diestel, Wegge & Schmidt, 2014).…”
Section: Introductionmentioning
confidence: 99%